2007
DOI: 10.1080/00103620701548977
|View full text |Cite
|
Sign up to set email alerts
|

Compost and Manure Effects on Fertilized Corn Silage Yield and Nitrogen Uptake under Irrigation

Abstract: Dairy manure increases the yields of dry bean (Phaseolus vulgaris L.) and spring wheat (Triticum aestivum L.) from eroded, furrow-irrigated soils and may increase corn (Zea mays L.) silage yield from steeper eroded areas under sprinkler irrigation. In a 2-year field study in southern Idaho on Portneuf silt loam (coarse silty, mixed, superactive, mesic Durinodic Xeric Haplocalcid), the effects of a one-time, fall application of 29 or 72 Mg ha 21 of dry manure or 22 or 47 Mg ha 21 of dry compost on subsequent si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Properties of the compost and manure applied each fall are shown in Table 2. Since dry matter (DM) contents are typically greater for compost than manure (Larney et al 2006;Lehrsch and Kincaid 2007), the identical DM between amendments in 2003 is somewhat surprising. The manure in 2003 may have been collected from an older or smaller stockpile, one that had lost more water to evaporation.…”
Section: Site Soils and Amendmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Properties of the compost and manure applied each fall are shown in Table 2. Since dry matter (DM) contents are typically greater for compost than manure (Larney et al 2006;Lehrsch and Kincaid 2007), the identical DM between amendments in 2003 is somewhat surprising. The manure in 2003 may have been collected from an older or smaller stockpile, one that had lost more water to evaporation.…”
Section: Site Soils and Amendmentsmentioning
confidence: 99%
“…This concentration of milk production in the region thereby concentrates the manure from the dairy cattle. Some of this manure, with nearly all of its N in organic forms (Lehrsch and Kincaid 2007), ideally can be used by crop producers as a substitute for relatively expensive conventional inorganic N fertilizers (Lehrsch et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the same soil as the current investigation, Turner et al (2004) (C) to N (C:N) ratio and concentrations of ammonium-nitrogen (NH 4 -N) and total C while increasing the electrical conductivity (EC) and concentrations of nitrate-nitrogen (NO 3 -N), FeO P (bio-available P), and TP, in general (Eghball et al 1997;Larney et al 2006). Composted dairy manure is often available for application to land used to produce high-value crops in irrigated areas (Sweeten 2000;Lehrsch and Kincaid 2007).…”
Section: Abstract: Center Pivot-erosion-infiltration-nutrient Lossesmentioning
confidence: 99%
“…Little research, in contrast, has studied changes in nutrient losses through longer time periods. Measuring runoff volumes and nutrient losses repeatedly through one or more growing seasons is needed (1) to adequately characterize constituent losses from manure or compost applications to agricultural areas across multiple time scales (Eghball et al 2002;Miller et al 2006;Macrae et al 2010); and (2) to document the effects of progressive seal and crust development in tilled soil (Neave and Rayburg 2007).Corn (Zea mays L.) silage yields and N uptake from the current study have been reported earlier (Lehrsch and Kincaid 2007). Yields in 2000 were similar among all rates of both amendments and the control.…”
mentioning
confidence: 99%
See 1 more Smart Citation